ANALISIS IMPLEMENTASI PENGELOLAAN SARANA DAN PRASARANA PENDIDIKAN DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA NEGERI 2 KRAKSAAN - PROBOLINGGO - jurnalpps pps; Subhan Subhan (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
The purpose of this study is to find out and analyze the implementation of the management of educational facilities and infrastructure, supporting and inhibiting factors, and the implementation of strategies carried out in the management of educational facilities and infrastructure in SMA Negeri 2 Kraksaan. In this study, researchers used a descriptive study with a qualitative approach. That is, data collected from interviews, field observations, and related documents. Data analysis in this study uses four components consisting of, data collection, data reduction, data presentation, and drawing conclusions. In this study the researchers analyzed by using triangulation to check the validity of the data / data credibility test. The results showed that the implementation of the management of educational facilities and infrastructure in SMA Negeri 2 Kraksaan was carried out quite well so that educational facilities and infrastructure could be optimally utilized in improving the quality of learning, with management concepts starting from the planning, procurement, storage, use, and elimination stages of facilities and infrastructure. Keywords: management, implementation, facilities and infrastructure, education